Effects of Alcohol and Acetate on Cerebral Blood Flow: A Pilot Study. (24th August 2019) - Tanabe, Jody; Yamamoto, Dorothy J.; Sutton, Brianne; Brown, Mark S.; Hoffman, Paula L.; Burnham, Ellen L.; Glueck, Deborah H.; Tabakoff, Boris
Abstract : Background: Acute alcohol produces effects on cerebral metabolism and blood flow. Alcohol is converted to acetate, which serves as a source of energy for the brain and is an agonist at G protein‐coupled receptors distributed in different cell types in the body including neurons. Acetate has been hypothesized to play a role in the cerebral blood flow (CBF) response after alcohol ingestion. We tested whether administration of acetate would alter CBF in a pattern similar to or different from that of alcohol ingestion in healthy individuals. Methods: Twenty‐four healthy participants were assigned by convenience to receive either 0.6 g/kg alcohol orally ( n = 12) or acetate intravenously ( n = 12). For each participant, CBF maps were acquired using an arterial spin labeling sequence on a 3T magnetic resonance scanner after placebo and after drug administration. Whole‐brain CBF maps were compared between placebo and drug using a paired t ‐test, and set at a threshold of p < 0.05 corrected for multiple comparisons ( k ≥ 142 voxels, ≥3.78 cm 3 ), voxel‐level p < 0.005. Intoxication was measured after placebo and drug administration with a Subjective High Assessment Scale (SHAS‐7). Results: Compared to placebo, alcohol and acetate were associated with increased CBF in the medial thalamus. Alcohol, but not acetate, was associated with increased CBF in the right orbitofrontal, medial prefrontal and cingulate cortex, and hippocampus. Plasma acetate levels increased following administration of alcohol and acetate and did not differ between the 2 arms. Alcohol, but not acetate, was associated with an increase in SHAS‐7 scores ( p < 0.001). Conclusions: Increased thalamic CBF associated with either alcohol or acetate administration suggests that the thalamic CBF response after alcohol could be mediated by acetate. Compared to other brain regions, thalamus may differ in its ability to metabolize acetate or expression of receptors responsive to acetate. Increased prefrontal and limbic CBF associated with alcohol may be linked to alcohol's behavioral effects. Abstract : Alcohol is metabolized to acetate, which serves as an energy source for the brain. Although acute alcohol is known to produce changes in cerebral blood flow (CBF), the effect of acetate on CBF has not been studied. Both alcohol and acetate were associated with an increase in thalamic CBF, suggesting that acetate could mediate the effects of alcohol in this brain region in controls. Increased frontal CBF with alcohol but not acetate may be linked to alcohol's behavioral effects.